A validation of neural co-activation as a measure of attentional focus in a postural task - Machado, Guilherme (2016)
Postural threat can induce conscious involvement in movement control. This internal focus has been implicated in compromising attentional processing efficiency during postural control, leading to behavioral adaptations that might increase the risk of falling in the elderly. It is suggested that electroencephalography (EEG) coherence, or ‘communication’, between T3 (verbal-analytical) and Fz (motor-planning) regions may provide an objective measure of internal focus in learned movement skills. However, it is currently unknown whether this experimental technique can be applied to the control of gait and posture; skills which develop early in life, without the use of declarative knowledge/explicit verbal cues to guide performance. We validate the utility of the EEG T3-Fz coherence analysis in a postural task. A total of 24 young adults produced small voluntary swaying movements in medial-lateral or anterior-posterior direction under conditions that directed their attentional focus either internally or externally. Although EEG coherence was sensitive to voluntary changes in attentional focus, the lack of observed between-group (High/Low-trait-reinvestment) difference in coherence may suggest that younger adults cannot be assumed to utilize explicit verbal cues to control voluntary postural sway unless explicitly instructed to do so. As a result, while these results indicate that EEG T3-Fz is a valid technique for assessing attentional focus in postural tasks, our data do not support the clinical application of this method of analysis in providing an objective indication of trait-reinvestment in tasks involving voluntary postural sway.